Manejo integrado del insecto taladrador Hypsipyla grandella en Plantaciones Forestales de Swietenia macrophylla - Valencia Tello, Raysa Nahomi (2020)
Swietenia macrophylla is a plantation of great importance since its wood has a high acceptance for the elaboration of different furniture and joinery, but it is affected by the damage that Hypsipyla grandella is causing to this timber. The present research aims to know the integrated pest management methods used to control H. grandella, and the damage it causes in Mahogany. The application of the different IPM controls and the benefits of each one on the timber plantation, avoiding causing economic losses to the producers of this wood, and raising awareness to be more environmentally friendly in the use of controls such as mechanical, cultural, biological, ethological and chemical. The conclusions of this research are projected to use the different types of controls where the economic threshold of the insect populations is kept at low levels, and where the control we apply has the least environmental impact on the plantation, natural resources and reducing production costs.